CEO Regulatory Focus, Analysts’ Optimism Bias, and Firm Strategic Change: Evidence From Chinese-Listed Companies - Huang, Chun; Zheng, Wangxiongjie (Frontiers in Psychology, 2022)
With the ongoing of Covid-19 pandemic, technological, socio-political, and institutional changes have led to a “new normal” competitive landscape, firms must make longer-term stra-tegic changes to deal with short-term discontinuities and great uncertainties to acquire sus-tainable advantage. Based on regulatory focus theory and upper echelons theory, this study explores the relationship between CEO regulatory focus and corporate strategic change and examines the moderating effects of analysts’ optimism bias in earning forecasts. The study uses data from A-share listed companies in China during 2010–2018. We find that CEO pro-motion focus is positively associated with strategic change, while CEO prevention focus is negatively associated with strategic change. We also find analysts’ optimism bias in earning forecasts would moderate these relationships.